6.Q. Workshop: Developing interventions to improve health and wellbeing of sexual and gender minority populations. (20th October 2021) - ,; ,
Abstract:  : In recent years, public health research has increasingly focused on identifying various risk factors purportedly leading to poor social, mental, and physical health among sexual and gender minorities (SGM). There is however, still a great paucity of research focusing on facilitators, barriers, and characteristics that may help inform the creation and implementation of successful and affirming interventions aimed at improving health outcomes in these communities. Building upon knowledge of implementation science, this workshop will showcase important aspects that need to be weighed when designing interventions for these communities. The definite strength of this workshop is the focus on lessons learned from theory-driven and evidence-supported intervention development processes, as well as from evaluation of implemented interventions and research results which highlight the efficacy of such interventions. These lessons have a great potential for further implementation across social and cultural contexts and can shape the design of future interventions. The presentations in this workshop will feature results from high-quality international studies focusing on SGM communities in Europe and the USA. Moreover, the presentations take into consideration various points of view (both from SGM individuals but also stakeholders, policy makers, and health care workers) and show results from studies across various stages of implementation (from intervention development, feasibility and baseline cross-sectional studies to evaluated interventions). With this balance in mind as well as limiting the number of presentations, ample time will be reserved for meaningful discussions with the audience and experts to gain further insight. Radhika Seiler-Ramadas will present qualitative results of a multi-center European study focusing on facilitators and barriers in implementing anti-discrimination interventions at the workplace. The results will include insights from both SGM youth as well as relevant stakeholders. Lovro Markovic will present results on the patient-physician relationship in trans and non-binary people who are undergoing medical transitioning and how these may improve their experiences in the healthcare system. Continuing with the patient-healthcare system interaction and further connections to care and community, Arjan van der Star will present results of a feasibility study focusing on the implementation of the patient navigation model in SGM youth and young adults focusing on prevention of suicide. Subsequently, Stefanie Kirchner will present results of a randomized controlled trial to reduce suicidality in SGM youth using video messages containing narratives from SGM persons themselves. Key messages: More work is needed to elucidate facilitators and barriers for successful design and implementation of interventions in sexual and gender minorities who are at greater risk for poor health. Understanding developments in implementation of public health interventions aiming at sexual and gender minorities is essential for reducing health inequities in this vulnerable population.